Changes in Endocan and Dermatan Sulfate Are Associated with Biomechanical Properties of Abdominal Aortic Wall during Aneurysm Expansion and Rupture - Metschl, Susanne; Bruder, Lukas; Paloschi, Valentina; Jakob, Katharina; Reutersberg, Benedikt; Reeps, Christian; Maegdefessel, Lars; Gee, Michael; Eckstein, Hans-Henning; Pelisek, Jaroslav (Thrombosis and Haemostasis, 2022)
Background and Aims The study aimed to assess the potential of proteoglycans (PGs) and collagens as serological biomarkers in the abdominal aortic aneurysm (AAA). Furthermore, we investigated the underlying mechano-biological interactions and signaling pathways.Methods Tissue and serum samples from patients with ruptured AAA (rAAA; n = 29), elective AAA (eAAA; n = 78), and healthy individuals (n = 8) were evaluated by histology, immunohistochemistry, and enzyme-linked immunosorbent assay, and mechanical properties were assessed by tensile tests. Regulatory pathways were determined by membrane-based sandwich immunoassay.Results In AAA samples, collagen type I and III (Col1 and Col3), chondroitin sulfate, and dermatan sulfate (DS) were significantly increased compared with controls (3.0-, 3.2-, 1.3-, and 53-fold; p < 0.01). Col1 and endocan were also elevated in the serum of AAA patients (3.6- and 6.0-fold; p < 0.01), while DS was significantly decreased (2.5-fold; p < 0.01). Histological scoring showed increased total PGs and focal accumulation in rAAA compared with eAAA. Tissue β-stiffness was higher in rAAA compared with eAAA (2.0-fold, p = 0.02). Serum Col1 correlated with maximum tensile force and failure tension (r = 0.448 and 0.333; p < 0.01, and r = 0.02), tissue endocan correlated with α-stiffness (r = 0.340; p < 0.01). Signaling pathways in AAA were associated with extracellular matrix synthesis and vascular smooth muscle cell proliferation. In particular, Src family kinases and platelet-derived growth factor- and epidermal growth factor-related proteins seem to be involved.Conclusion Our findings reveal a structural association between collagen and PGs and their response to changes in mechanical loads in AAA. Particularly Col1 and endocan reflect the mechano-biological conditions of the aortic wall also in the patient's serum and might serve for AAA risk stratification.
Keywords: abdominal aortic aneurysm; biomarkers; proteoglycans; endocan; dermatan sulfate